2005
DOI: 10.1016/j.jmwh.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of and Response to Postpartum Hemorrhage in Rural Northern India

Abstract: This study describes the results of a Morbidity and Performance Assessment (MAP) conducted to provide insight into the medical factors contributing to maternal and newborn morbidity and mortality in a rural district of northern India, and to use these insights to develop a locally appropriate, community-based safe motherhood program The MAP study was based on verbal autopsy method. Five hundred ninety-nine women (or in the case of 9 maternal deaths, a family member) participated in the study. This article desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Returning to the Delay Model, a theoretical and practical issue raised in this study is the relative contribution of health-related beliefs, individual attributes, and socioecological constraints to care and care-seeking for obstetric emergencies. This represents a relatively-unexplored agendum in safe motherhood (8-9). Addressing this agendum is necessary if we are to improve programming to reduce maternal death and disability during the transition to skilled birth attendance for all women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Returning to the Delay Model, a theoretical and practical issue raised in this study is the relative contribution of health-related beliefs, individual attributes, and socioecological constraints to care and care-seeking for obstetric emergencies. This represents a relatively-unexplored agendum in safe motherhood (8-9). Addressing this agendum is necessary if we are to improve programming to reduce maternal death and disability during the transition to skilled birth attendance for all women.…”
Section: Discussionmentioning
confidence: 99%
“…This presents a daunting challenge for global safe motherhood. Targeting PPH in these vulnerable populations with effective, culturally-appropriate interventions is necessary to achieve Millennium Development Goal 5, which aims at reducing maternal mortality by 75% by 2015 (6-9). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among Chinese speaking individuals in Australia with anxiety disorders, the most frequently endorsed reason for seeking out formal services was problem recognition (Ho et al, 2008). Mismatches between “lay” and “expert” diagnoses have been associated with the length of untreated psychosis or other mental health problems (Bergner et al, 2008) and for postpartum hemorrhage documented in rural India (Sibley et al, 2005). While not fully consistent, this research suggests the need to consider controls.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another study done in rural Bangladesh reported that approximately 67% of the study participants perceived a delay in deciding to seek care, while 12% and 24% perceived delays in access to transportation and in reaching the providers for care, respectively [15]. While, a study from northern India found that low levels of health seeking was associated with poor problem recognition before and after delivery [16]. Postpartum care utilization has also been linked with the perceived nature and severity of the problem, [17] and socio-cultural factors, such as practice of seclusion [18][19][20].…”
Section: Introductionmentioning
confidence: 99%